2006
DOI: 10.1111/j.1600-0722.2006.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Minor salivary gland secretion rates and immunoglobulin A in adults and the elderly

Abstract: Previously published data are conflicting about the effect of various factors on secretions from minor salivary glands. The aim of the present study was to investigate the secretion rate from palatal, buccal, and labial glands, and to analyze the immunoglobulin A (IgA) concentrations in relation to age, gender, circulatory disease, diabetes, medication, smoking, and pregnancy. Resting and stimulated whole-saliva secretion rates, as well as IgA concentration in stimulated whole saliva, were also examined. One-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 34 publications
8
65
1
3
Order By: Relevance
“…Previous studies suggest that there may be age and gender related differences in salivary gland function (1)(2)(3)(4)(5). However, the limited and often conflicting information available from healthy populations makes it difficult to confirm these differences (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest that there may be age and gender related differences in salivary gland function (1)(2)(3)(4)(5). However, the limited and often conflicting information available from healthy populations makes it difficult to confirm these differences (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Both age and gender associated differences in the structure and function of salivary glands have been identified (1,4). Examples of such differences include a decrease in gland size and weight (15), decreased saliva flow rate (1)(2)(3), and an increased concentration of immunoglobulin A (IgA) (3). In humans, decreases in protein synthesis (16) and salivary flow rate (1,2,4,5) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Muchos estudios, como el presente, han mostrado índices de caries más altos en mujeres que en hombres (26) , lo cual puede ser explicado por la influencia de factores de riesgo como: menor flujo salival (27) , diferentes hábitos dietéticos, variaciones genéticas, y asociación con mayor prevalencia de enfermedades sistémicas (28) . Para la autopercepción de salud oral, no se encontraron variables asociadas a la excelente y muy buena autopercepción de salud oral, por lo cual es necesario seguir estudiando este aspecto que puede contribuir a mejorar las actividades preventivas en esta población.…”
Section: Discussionunclassified
“…Therefore, decreased levels of SIgA contribute to higher susceptibility of elderly to this kind of infections. Studies carried out in elderly people reported lower SIgA secretion rates at rest both in women and in men [41,15].…”
Section: Secretory Immunoglobulin-amentioning
confidence: 99%